UNDERGROUND MINING OF A FROZEN PLACER DEPOSIT IN THE ARCTIC - Kirzhner F.; Sherstov V.; Ilkovskii K.; Gurov S.; Mordvov M.; Sytnik Y. (My University, 2001)
The Sakha Republic (Yakutia) is the northern frontier territory of Russia, located partly above the Arctic Circle. It holds important natural mining resources for the country's current and future economic development. A wide range of deposits was discovered here, and large sums were invested in infrastructural development. This paper has two complementary aims: Description of the present and future potential of tin-bearing deposits. Some special suggestions for mining works management in a frozen placer.